Penguatan Pendidikan Karakter dalam Pembelajaran Berbasis Hots Character Education Strengthening in Hots-Based Learning - Hayani, Aida; Fahmi, Fauzi; Putri Marpaung, Rida Chairani (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2020)
The problematic phenomenon of the increasing cases of juvenile delinquency that arises today, both in terms of quantity and quality can be used as a measurement of the decline in ethics, morals and character of the nation as the originator of the golden generation of the future. This phenomenon certainly cannot be separated from the role of education, especially education in schools/madrasas. In connection with this phenomenon the government promotes the strengthening of character education to overcome existing problems. The current 2013 curriculum is a government effort to improve the existing system. Improvements are made by changing the content standards and process standards. The hope of the government with curriculum changes can help students to improve their ability to think creatively and innovatively at a high level in preparing young people who excel to face global challenges. This study aims to change the new paradigm in learning that emphasizes the strengthening of HOTS-based character education in order to produce superior generations of the digital age. This study used a qualitative approach with case study design. Data collection techniques through observation, interviews and documentation. High-level abilities can be realized by practicing through learning in the classroom. Supporting learning to improve the ability to think highly is through contextual and meaningful learning.